English Study Program Students’ Perception on Using Grammarly as an Online Grammar Checker in Academic Writing - Putri, Syafira; Erni, Erni; Masyhur, Masyhur (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
Grammarly as an online grammar checker is a new experience for English students. Based on the interviewed results of information to students, it is found that Grammarly useful in academic writing. The research in this paper aims to find out English study program students’ perception on using grammarly as an online grammar checker in academic writing. The research design is mixed methods (quantitative and qualitative). Technique of data validation through a questionnaire and interview. Purposive sampling was used to select the research sample, which involved 37 students. Ten students were interviewed for the qualitative data. The findings indicate that the students had a high perception on using Grammarly as an online grammar checker in academic writing. In accordance with that, the results of the qualitative data also show positive responses that Grammarly can be useful, efficient, and comfortable as an online grammar checker for students in academic writing.